Ubiquinol-induced gene expression signatures are translated into altered parameters of erythropoiesis and reduced low density lipoprotein cholesterol levels in humans - Schmelzer, Constance; Niklowitz, Petra; Okun, Jürgen G.; Haas, Dorothea; Menke, Thomas; Döring, Frank (IUBMB life, 2011)
Studies in vitro and in mice indicate a role for Coenzyme Q10 (CoQ10) in gene expression. To determine this function in relationship to physiological readouts, a 2-week supplementation study with the reduced form of CoQ10 (ubiquinol, Q10H2, 150 mg/d) was performed in 53 healthy males. Mean CoQ10 plasma levels increased 4.8-fold after supplementation. Transcriptomic and bioinformatic approaches identified a gene-gene interaction network in CD14-positive monocytes, which functions in inflammation, cell differentiation, and peroxisome proliferator-activated receptor-signaling. These Q10H2-induced gene expression signatures were also described previously in liver tissues of SAMP1 mice. Biochemical and NMR-based analyses showed a reduction of low density lipoprotein (LDL) cholesterol plasma levels after Q10H2 supplementation. This effect was especially pronounced in atherogenic small dense LDL particles (19-21 nm, 1.045 g/L). In agreement with gene expression signatures, Q10H2 reduces the number of erythrocytes but increases the concentration of reticulocytes. In conclusion, Q10H2 induces characteristic gene expression patterns, which are translated into reduced LDL cholesterol levels and altered parameters of erythropoiesis in humans. © 2011 IUBMB IUBMB Life, 63(1): 42-48, 2011
Gesehen am 12.10.2022